2008
DOI: 10.1002/adfm.200800444
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pass‐Band Optical Left‐Handed Metamaterials Based on Random Dendritic Cells

Abstract: Left‐handed metamaterials (LHMs) composed of random dendritic cells demonstrate a multi‐band resonance and negative refractive index. A nano‐assembly approach is established to fabricate optical LHMs. Random nanostructures of silver dendritic cells are prepared and further fabricated into a sandwich‐like structure with a dielectric medium. The dentritic nano‐assembled configuration reveals a multi‐band resonance and a high intensity of the pass‐band at infrared frequencies, and can be facilely and cheaply prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…Chen et al [54] demonstrated a metamaterial with two domains of the negative refraction due to two different sizes of the resonators. Liu et al [55] and Zhao et al [56] realized a metamaterial with multiresonant left-handed behavior from a material made of silver dendritic cells. Such an approach can increase the number of frequency regimes over which useful metamaterial responses are obtained.…”
Section: Metallodielectric Compositesmentioning
confidence: 99%
“…Chen et al [54] demonstrated a metamaterial with two domains of the negative refraction due to two different sizes of the resonators. Liu et al [55] and Zhao et al [56] realized a metamaterial with multiresonant left-handed behavior from a material made of silver dendritic cells. Such an approach can increase the number of frequency regimes over which useful metamaterial responses are obtained.…”
Section: Metallodielectric Compositesmentioning
confidence: 99%
“…The previous paper [4] reported that negative l 0 existed at high f for the anisotropic iron nanorods, which slightly crosslinked together, but it disappeared when the anisotropic iron nanorods were transformed into isotropic nanoparticles. The random nanostructures of silver dendritic cell could constitute left-handed metamaterials at infrared frequencies [20]. In this experiment, the obtained dendritic iron could be regarded as a micropine where many 1D nanorods paralleled to each other and were linked together with a 1D trunk, so the negative l 0 occurred.…”
Section: Microwave Electromagnetic Properties Of the Dendritic Ironmentioning
confidence: 99%
“…Owing to the peculiar structure and morphology anisotropy, the dendritic fractals exhibit different properties from the nano-/microparticles with shape isotropies and have wide applications in the fields of the design and synthesis of new nano-/microfunctional materials [12,19]. It has been predicted that dendritic fractals may have negative permittivity and permeability and are possibly used as left-handed metamaterials (LHM) [20], resulting in peculiar electromagnetic properties and excellent microwave adsorption property. Recently, dendritic FeNi 3 alloys with a single crystalline trunk or branch were reported to be synthesized in a large scale through a hydrothermal method, which was claimed to have a DLA formation mechanism, similar to that of dendritic hematite [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the fabrication of gradient index lens is relatively complicated, and they can only realize limited phase shifts. Recent investigations in metamaterials have opened up new avenues for manufacturing various novel devices [6][7][8][9][10][11][12][13], in which the electromagnetic metasurface as a new approach has attracted tremendous interests of researchers [14][15][16][17][18][19]. The arbitrary modulation of electromagnetic waves could be realized just via ultrathin artificial composite materials, including bending of the direction of propagating waves, abnormal transmission and reflection, and planar lenses.…”
Section: Introductionmentioning
confidence: 99%